Exploring the Path of Cultivating Cross Cultural Competence among Engineering Students in Higher Education Institutions in the Context of Globalization (Journal of humanities and social sciences exploratio, 2026)
In the era of globalization and the deepening of the "the Belt and Road" initiative, intercultural communication ability has become one of the core qualities of high-quality engineering and technical personnel. This article is based on interdisciplinary theoretical perspectives such as philosophy and cultural studies, education, sociology, psychology, and cross-cultural communication, exploring the necessity, practical challenges, and systematic paths for cultivating cross-cultural competence among engineering majors such as mechanical engineering in Chinese universities. The article first examines the enlightenment of cultural relativism and universalism on engineering ethics from a philosophical perspective, and then analyzes the weak current situation of humanistic literacy and cross-cultural awareness cultivation in current engineering education. Combining sociological theories on social interaction and integration, psychological research on cultural adaptation and identity, and educational theories on ability construction, this article proposes a cross-cultural competence model for engineering students that includes three dimensions: cognition emotion behavior. Finally, the article constructs a comprehensive training program aimed at deeply integrating professional education and cross-cultural general education from multiple aspects such as curriculum system reconstruction, campus culture creation, practical platform expansion, evaluation mechanism innovation, and counselor role reshaping, in order to provide theoretical reference and practical guidance for the comprehensive development and social adaptation of new generation engineering talents.